Myeloid-derived suppressor cells and vaccination against pathogens - Prochetto, Estefanía; Borgna, Eliana; Jiménez-Cortegana, Carlos; Sánchez-Margalet, Víctor; Cabrera, Gabriel (Frontiers in Cellular and Infection Microbiology, 2022)
It is widely accepted that the immune system includes molecular and cellular components that play a role in regulating and suppressing the effector immune response in almost any process in which the immune system is involved. Myeloid-derived suppressor cells (MDSCs) are described as a heterogeneous population of myeloid origin, immature state, with a strong capacity to suppress T cells and other immune populations. Although the initial characterization of these cells was strongly associated with pathological conditions such as cancer and then with chronic and acute infections, extensive evidence supports that MDSCs are also involved in physiological/non-pathological settings, including pregnancy, neonatal period, aging, and vaccination. Vaccination is one of the greatest public health achievements and has reduced mortality and morbidity caused by many pathogens. The primary goal of prophylactic vaccination is to induce protection against a potential pathogen by mimicking, at least in a part, the events that take place during its natural interaction with the host. This strategy allows the immune system to prepare humoral and cellular effector components to cope with the real infection. This approach has been successful in developing vaccines against many pathogens. However, when the infectious agents can evade and subvert the host immune system, inducing cells with regulatory/suppressive capacity, the development of vaccines may not be straightforward. Notably, there is a long list of complex pathogens that can expand MDSCs, for which a vaccine is still not available. Moreover, vaccination against numerous bacteria, viruses, parasites, and fungi has also been shown to cause MDSC expansion. Increases are not due to a particular adjuvant or immunization route; indeed, numerous adjuvants and immunization routes have been reported to cause an accumulation of this immunosuppressive population. Most of the reports describe that, according to their suppressive nature, MDSCs may limit vaccine efficacy. Taking into account the accumulated evidence supporting the involvement of MDSCs in vaccination, this review aims to compile the studies that highlight the role of MDSCs during the assessment of vaccines against pathogens.